The Effect of Adding Koro Benguk (Mucuna pruiriens (L). Dc.) on Acceptance and Physical Properties of Ice Cream - Achsanta Khalqie; Eva Fitriyaningsih (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2022)
Ice cream is a frozen food product made through a combination of freezing and agitation processes. Adding koro benguk beans will increase the ice cream's nutritional value, especially fiber. This research aims to determine the effect of the addition of Koro Benguk Beans (Mucuna pruriens (L). Dc.) on acceptance, physical properties, and tests for ice cream fiber content. Research methods included experiments to see the effect of adding koro benguk beans to ice cream on acceptability, including color, aroma, texture, and taste, as well as physical properties, including overrun, melting speed, and the ice cream emulsion stability test. The method used was the completely randomized design (CRD) non-factorial with 3 treatments; the addition of koro benguk beans was 30 g, 40 g, and 50 g of the total milk used with three repetitions each. Based on the ANOVA analysis, the following organoleptic test results were found: (1) on color, the highest value was 3.89 (like); (2) on taste, the highest value was 3.89 (like); (3) on aroma, the highest value was 3.70 (like); and (4) on texture, the highest value was 3.65 (like). Meanwhile, for the physical test, the following results were found: (1) on overrun, the highest value was 23.07; (2) on melting speed, the highest value was 8.09; (3) on emulsion stability, the highest value was 32.13; and (4) on fiber content, the highest value was 1.43. The addition of 30 g, 40 g, and 50 g of koro beans significantly affected the panelists' preference level, physical properties, and fiber content of ice cream. It is hoped that further research on koro bean ice cream will lead to the processing of koro bean porridge being better filtered to produce a smoother texture.